Pemahaman Guru Bahasa Indonesia SMP, SMPIT, dan MTs tentang Pembelajaran Bahasa Indonesia di Kecamatan Sekongkang Kabupaten Sumbawa Barat - Fahmi Fahlizi; Johan Mahyudi; Burhanuddin (Jurnal LENTERA: Jurnal Studi Pendidikan, 2022)
This study aims to obtain information about the understanding of Indonesian language teachers at SMP, SMPIT, and MTs in Sekongkang Subdistrict, West Sumbawa Regency towards text-based Indonesian language learning. This type of research is descriptive research using qualitative and quantitative approaches. The targets in this study were Indonesian language teachers at SMP, SMPIT, and MTs in Sekongkang Subdistrict, West Sumbawa Regency. The method used in the process of collecting data in this research is the listening method and the speaking method. While the method used in data analysis is the intralingual equivalent method of the HBB, HBS, and HBSP techniques. Based on the results of the analysis, it was found that the understanding of Indonesian language teachers in SMP, SMPIT, and MTs towards text-based Indonesian language learning was categorized as being able to understand the types of texts based on their genres. From the point of view of the structure of the text, the teacher is also able to understand the structure of the text based on its genre. The understanding of Indonesian language teachers at SMP, SMPIT, and MTs towards text-based Indonesian language learning is less able to understand the use of linguistic tools in the text. And lastly, the understanding of Indonesian language teachers at SMP, SMPIT, and MTs towards text-based Indonesian language learning has been able to understand the social objectives in the text, because most of the respondents are less able to describe their understanding in text based on the genre